The Implementation of Flip Book-Based Audio-Visual Media in the Learning Basketball Lay-Up Shoot - Yopi Meirizal; Sumbara Hambali; Dhani Agusni Zakaria; Yudi Hidayat; Dindin Bernhardin (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
Objective. Many universities have reported that the basketball learning process is unstimulating and repetitive. This study aims to introduce a novel approach to basketball learning by investigating the impact of flip book-based audio-visual media on the learning outcomes for lay-up shots in basketball games. The research will focus on determining the effectiveness of this approach in enhancing the learning process and improving the overall performance of players in basketball games. Materials and Methods. The study employed a one-group pretest-posttest design with an experimental approach to examine the effects of basketball learning courses on the lay-up shoot skills of 30 students belonging to the PJKR STKIP Pasundan Class of 2021. Cluster random sampling was used to select the participants from the original population of students. A test was conducted to evaluate the movement process of basketball lay-up shoot skills, and the data analysis was performed using a t-test approach with the IBM SPSS 25 program. Result. The study's findings revealed a statistically significant difference between the pretest and posttest values. The average value of the difference was -1.371, with a standard deviation of 0.907, and a calculated t-value of -11.575 with a degree of freedom of 29. The significance value obtained (2-tailed) was 0.000, indicating that the difference was significant at 0.05. The posttest value was greater than the pretest value. Conclusion. Based on the findings, it can be inferred that fundamental lay-up shooting skills in basketball games can be significantly enhanced through the utilization of flip book-based audio-visual media. This suggests that there is a need for educational instructors, including lecturers, teachers, and students alike, to adopt innovative teaching approaches that promote student motivation and optimize teaching and learning interactions.